DIGITAL TRANSFORMATION OF THE GLOBAL EDUCATION MARKET - Tsymbal, Liudmyla; Kalenyuk, Iryna (Baltic Journal of Economic Studies, 2023)
The global education market is undergoing significant changes due to modern digitalisation. The latest technologies are significantly changing learning technologies, the structure of education, international flows and their volume in general. The subject of the study is to assess the impact of digital transformation on the global world market. The aim of this article is to analyse the development processes of the global market for educational services in the context of modern challenges, in particular digital transformation, and its consequences for the higher education market. The methodology of the study included research, a review of scientific literature, graphic visualisation of digitalisation. The methods of system analysis and generalisation have made it possible to identify the main directions of transformation of the global and regional educational markets, to characterise the dynamics of the spread of the latest forms of education and the growth of their profitability, to confirm the turbulence and instability of internationalisation trends and the intensification of competition between traditional and new providers of educational services. Research has shown that the online education sector is developing and expanding rapidly. The amount of capital raised and its profitability are increasing, confirming the prospects of these investments. There is a growing variety of online education providers, which generally creates significant competition for traditional institutions such as universities. Educational products are becoming more diversified and there is a growing trend towards personalised and adaptive learning on online educational platforms using artificial intelligence and machine learning technologies. In recent years, there has been a significant increase in the number of students enrolled in various online courses, and there is a growing demand for distance learning and flexible, personalised learning options. The global education market is characterised by unstable dynamics of internationalisation due to various external factors such as the COVID-19 pandemic, military aggression, demographic factors, political and economic instability. Competition between traditional and new providers for students, market share and financial resources is intensifying. In general, despite the negative factors, the number of foreign students tends to increase, albeit rather unevenly across countries. The widespread use of ICT in education and other activities can pose potential threats and challenges: increased competition and lower quality of education, spread of unwanted and anti-social information.